El influjo de los artistas franceses en la época romántica - Pereira, Eugenio (Revista Chilena de Humanidades, 2015)
Eugenio Pereira Salas, the late noted historian, makes a survey of the work of French architects, sculptors, painters and lithographers in Chile, from the middle of the 19th Century onwards. His article establishes the influence they exerted upon the growth of the arts in our country, as well as their gravitation in the development of the national culture, which the author sees as the result of the interaction of the spiritual forces of both countries.